Innovation, learning and performance in a resource-rich emerging economy - Gregory J. Scott; Ian Chaston (South African Journal of Business Management, 2018)
Background: This article compares the performance of firms in resource-rich sectors of the Peruvian economy with that of businesses operating in service sectors. Objectives: In so doing, the research seeks to examine whether innovation is managed differently by firms operating in different sectors of a developing-country economy and whether the performance of firms in an emerging economy may be influenced by innovation and learning practices at the sectoral level. Method: Data were acquired through a survey of overwhelmingly middle managers working in Peru. Results: According to the survey findings, the performance of firms in the resource-rich sectors appeared to be uninfluenced by innovation or involvement in organisational learning. In contrast, firms in the service sectors not only exhibited an innovation orientation and involvement in learning but also reported higher sales growth. Conclusion: The study concludes that firms operating in the resource-rich sectors of Peru's economy do not appear to benefit from engaging in innovation or learning at this point in time, whereas such activities are advantageous for service sector businesses. Therefore, the relationship between innovation, learning and performance may be influenced not just by the type of economy but also by the sector in which the firms are operating.
Keywords: 650